"Geographies of Peoples": Scientific Racialism and Labor Internationalism in Gilded Age American Socialism. (8th March 2019) - Costaguta, Lorenzo
Abstract: This article investigates ideas of race in Gilded Age socialism by analyzing the intellectual production of the leaders of the Socialist Party of America (SLP) from 1876 to 1882. Existing scholarship on socialism and race during the Gilded Age and the Progressive Era rarely addresses socialist conceptions of race prior to 1901 and fails to recognize the centrality of scientific racialism and Darwinism in influencing socialist thought. By positioning American socialism within a transatlantic scenario and reconstructing how the immigrant origins of Gilded Age socialists influenced their perceptions of race, this article argues that scientific racialism and Darwinism competed with color-blind internationalism in shaping the racial policies of the SLP during the Gilded Age. Moreover, a transatlantic investigation of American socialist ideas of race presents a reinterpretation of the early phases of the history of the SLP and addresses its historical legacies. While advocates of scientific racialism and Darwinism determined the racial policies of the SLP in the 1880s, color-blind internationalists abandoned the party and extended their influence beyond organized socialism, especially in the Knights of Labor.